Satisfaction with a new patient education program for children, adolescents, and young adults with differences of sex development (DSD) and their parents. - Sabine Wiegmann; Ralph Schilling; Mirja Winter; Martina Ernst; Katja Wechsung; Ute Kalender; Barbara Stöckigt; Annette Richter-Unruh; Olaf Hiort; Ulla Döhnert; Louise Marshall; Julia Rohayem; et al. (Elsevier, 2024)
Objective: Evaluation of the participant satisfaction with a newly developed interdisciplinary, modular education program for children, adolescents, and young adults with differences of sex development (DSD) and their parents. Methods: The two-day program including tailored medical information, peer consultation and psychological support aimed to improve diagnosis-specific knowledge and empowerment. Post-training satisfaction was measured using an adapted ZUF-8 questionnaire, scoring from 5 (worst) to a maximum of 26 (best) for persons aged 6-17 and from 10 to 40 points for adults, including 2 open-ended questions. Results: The questionnaire, completed by 89 children (6-13 years), 92 adolescents (14-17 years), 47 young adults (18-24 years), and 345 parents, revealed consistent high satisfaction with the program regardless of age or diagnosis (children 24.4 ± 2.1, adolescents 23.5 ± 2.7; young adults 36.0 ± 4.0, parents 36.6 ± 3.4). Neither sociodemographic factors nor diagnosis burden, shame, or informedness showed relevant associations with satisfaction levels. Participants highlighted exchange and open atmosphere as key satisfaction elements. Conclusion: Satisfaction with the new education program was high in all examined groups. Implementing it in routine care requires further analysis to determine the program's long-term effects on well-being and knowledge. Innovation: The first educational program for young people with DSD addressing their specific challenges through inclusive language, an open approach to sex and gender and the inclusion of self-help groups.